Three Classical Japanese Literary Images Recited in the Noli Drama and Retroactive in the Tale of Genji - Švambarytė, Dalia (Acta Orientalia Vilnensia, 2002)
Classical Japanese literature is rich in allusions and multi-connotation images that migrate freely in Japanese or Chinese-written works. A hint dropped by the author and adequately perceived by the reader adds new dimensions to the text, endows it with further arguments and may be essential in dealing with characters and true motivation of their behaviour. The Noh drama was chosen in this essay as a genre that conveys concentrated emotion and through it reveals the very essence of the meaning of certain symbols agreed in medieval Japanese literature. Translated passages from ancient and medieval Japanese and Chinese sources, and extracts from Miwa, The Cloth-Beating Block, Lady Han as the central Noh plays discussed here enable us to look retrospectively at the setting of certain scenes and dialogues in Murasaki Shikibu’s The Tale of Genji where details minor in scale may be major in significance and play the key role in the emotional undercurrent of the novel as does the white fan in the relationship of Genji with Lady of the Evening Faces, the thump of fulling hammers in the circumstances of her death, and the shadow of Mt. Miwa in the portrait of Rokujo Lady whose inclusive appearance links together the issues of this article.